Economic liberalism, social disparities and poverty in underdeveloped countries (1994)
Following the radical programs of economic adjustment, international agencies and governments in Latin America have been shaping their policies to protect the very poor, either by compensating for a deterioration in standards of living to which they themselves had contributed to, or simply to avoid further social unrest. Today, the idea that the government should intervene to resol ve problems of poverty and disparity is accepted; but it is accepted from a liberalstandpoint, that is to say, expeling politics from the equation and giving the market free rein to regulate society. In this view, policy to protect the poor makes the State some kind of charitable organization, a safety-net for those shut out of the market. This is based on two principIes: be patient, wait till tomorrow. These principIes are to be found in Rawls and in Hayek, who differ on some matters but agree on four main themes: the decisive role of the market in forming society, the justification of the fetishism of commodities, the creative disparities and the social exclusion as an individual phenomenon.